2014
DOI: 10.1007/s00247-014-2875-6
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tears in children and adolescents: experience at a large pediatric hospital

Abstract: Rotator cuff tears can be identified during MRI examination of symptomatic child and adolescent shoulders and often consist of tear patterns associated with repetitive microtrauma in overhead athletic activities or with single traumatic events. Rotator cuff tears are seen throughout the range of skeletal maturity, often coexist with labral tears and typically are found in athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
3
27
1
1
Order By: Relevance
“…Our small sample differed in that we found more intrasubstance tears than articular-side tears (4 compared with 2) and no bursal-side tears were observed. The majority of our partial-thickness tears were at the insertion which is similar to the findings reported from a recent study of 201 able-bodied pediatric participants [16]. Tendon tears at the insertion site have been attributed to younger populations, and in the nonwheelchair adult population, the critical zone has been found to be the most common site of tears [1921].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our small sample differed in that we found more intrasubstance tears than articular-side tears (4 compared with 2) and no bursal-side tears were observed. The majority of our partial-thickness tears were at the insertion which is similar to the findings reported from a recent study of 201 able-bodied pediatric participants [16]. Tendon tears at the insertion site have been attributed to younger populations, and in the nonwheelchair adult population, the critical zone has been found to be the most common site of tears [1921].…”
Section: Discussionsupporting
confidence: 85%
“…Our finding that supraspinatus tears were more common than tears in the infraspinatus, subscapularis or long head of the biceps tendon was similar to shoulder imaging findings from able-bodied adult and pediatric populations [16, 17]. This is interesting as it implies that while wheelchair use increases the frequency of rotator cuff symptoms and tearing, it may not be a different location or tear type from nonwheelchair users.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Sixteen studies (53%) were conducted prospectively; one study did not mention time of enrollment. Ten studies reported abnormalities in asymptomatic volunteers 1,11,16,18,21,23,24,33,39,47 ; 5 studies (4 of which were cadaver studies) reported prevalence in the general population 10,14,26,28,49 ; 8 included symptomatic patients 6,7,31,36,44,46,50,51 ; and 7 described patients with acute or chronic shoulder dislocations. 3,27,29,38,42,43,52 The majority of the studies used ultrasound to image the rotator cuff (43%; 13 of 30).…”
Section: Study Characteristicsmentioning
confidence: 98%
“…MR arthrography also has similar sensitivities and specificities for detecting such lesions in adolescent patients, in comparison with adults (21). Differences in chronic injuries for pediatric patients include the rare occurrence of rotator cuff pathologic conditions and the relatively high likelihood of finding labral pathologic conditions involving the posterior and superior labrum (four of every five injuries seen with shoulder arthroscopy) (22). Injury patterns that are exclusive to adolescent athletes are Little Leaguer's shoulder and acromial apophyseolysis.…”
Section: Shoulder Injuriesmentioning
confidence: 99%